Pengaruh Komposisi Bahan Baku dan Kadar Perekat Tepung Tapioka Terhadap Kualitas Briket dari Campuran Daun Ketapang dan Tempurung Kelapa - Hanan Izdihar Rashif Hunsa; Rosita Dwityaningsih; Ilma Fadlilah; Zhilal Shadiq; Sari Sekar Ningrum (Infotekmesin, 2025)
Ketapang leaves are an example of biomass that can be used to make briquettes. However, ketapang leaves produce a low calorific value, so they require additional ingredients to increase the calorific value, one of which is coconut shell. This research aims to evaluate how variations in raw material composition and adhesive content of tapioca flour affect the quality of briquettes on the parameters of calorific value, water content, ash content, volatile substances, fixed carbon content, and density. The method applied in this research involved mixing ketapang leaf charcoal and coconut shell charcoal, then adding adhesive in the form of tapioca flour. The study results showed that all the briquettes tested met SNI 8966-2021 standards except for the density parameter. The conclusion of this study is that the greater the composition of the briquette raw materials and the lower the adhesive content of tapioca flour, the better the quality of the briquettes. The mixed briquettes that produce the best quality are composed of 20% Ketapang leaf charcoal and 80% coconut shell charcoal. The tapioca flour adhesive that delivers the best quality briquettes is at a percentage of 5%.